Aplicação Móvel para Gestão de um Programa de Afiliados - André Leão da Costa Baldaque Marinho (2013)
A large part of the infrastructure that we know as Internet is supported by income from advertising campaigns. An affiliate program is a type of performance-based marketing in which a company rewards one or more affiliates for each visitor or customer brought by the affiliate's marketing efforts. This marketing strategy is based on four key roles: the advertiser who wants to promote a service or product, the affiliate platform that contains the advertisers' campaigns for the affiliate to choose from, the affiliate that promotes campaigns on their websites, and the customer who, by clicking on an advertisement, filling out a form, or making a purchase, generates a commission for the affiliate.As the largest affiliation platform in Portugal, Netlucro manages hundreds of online advertising campaigns for several advertisers and agencies. However, the growing trend of using mobile devices instead of traditional computers incited the need for a mobile application capable of allowing affiliates to manage their account on the platform anywhere using their smartphone.This dissertation is focused on the planning and development of a mobile application that enables affiliates to get updated strategic information for efficiently managing their business. The developed application allows the affiliates to check advertisers' campaigns and distribution channels, as well as monitoring the progress of their results graphically. In addition to the mobile application, a communication module with the existing system was also developed, as well as an automatic notification service (PUSH) which warns affiliates of relevant events in an efficient way through their smartphone.